Pengaruh Profitability, Leverage, Corporate Size, dan Capital Intensity Terhadap Effective Tax Rate - Zaidan, Ismail Nur; Cahyono , Yuli Tri (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
The purpose of this study is to analyze the effect of profitability, leverage, corporate size, and capital intensity on an effective tax rate (ETR). This type of research is quantitative, with secondary data. The data used is in the form of annual financial reports from manufacturing companies in the consumer goods industry sector for the 2018-2020 period. The data source for this research was obtained from the Indonesia Stock Exchange (IDX) website. The variable in this study is ETR, profitability, leverage, corporate size, and capital intensity. The data analysis method is descriptive statistical analysis. The results showed that the variables of profitability, leverage, and corporate size have an effect, while the capital intensity variable does not affect the ETR.